2019
DOI: 10.1108/scm-10-2018-0375
|View full text |Cite
|
Sign up to set email alerts
|

The role of absorptive capacity within supply chain quality integration

Abstract: Purpose There is a consensus suggesting that the theoretical underpinning associated with supply chain quality management practices remain evolutionary to current thinking. Therefore, this study aims to explore how absorptive capacity (AC) supports supply chain quality integration (SCQI) by building product and process quality within a supply chain (SC). Design/methodology/approach A comparative case study of global pharmaceutical manufacturers in a developing market was undertaken. A two-round qualitative r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
2
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(46 citation statements)
references
References 103 publications
1
40
2
3
Order By: Relevance
“…The dimensions are built upon the observation, emanating from the body of extant research, that IDCs are discussed and identified in terms of who (Alkalha et al, 2019;Junfeng & Wei-Ping, 2017;Kumar et al, 2018;Lichtenthaler, 2008;Lopez et al, 2012;L€ utjen et al, 2019;Monferrer et al, 2015;Petricevic & Verbeke, 2019;Rajaguru & Matanda, 2019;Rebs et al, 2019;Robertson et al, 2012;Saenz et al, 2014;Vanpoucke et al, 2014;Weerawardena et al, 2015;Zheng et al, 2011) Resource exploitation -Supplier integrative capability -Knowledge acquisition and evaluation -Market-focused learning capability Relationship governance Boundary management -Networking capability -Supplier relationship management capability -Business relationship process management (Allred et al, 2011;Cui et al, 2018;Fehrer & Nenonen, 2020;Forkmann et al, 2016;Helfat & Raubitschek, 2018;Mitrega et al, 2012Mitrega et al, , 2017Mitrega & Pfajfar, 2015;Ngasri & Freeman, 2018;Nordin et al, 2018 (Beske, 2012;Beske et al, 2014;Butler & Soontiens, 2015;Choi et al, 2019;Gruenberg-Bochard & Kreis-Hoyer, 2009;M€ oller & Svahn, 2003M€ oller & Svahn, , 2006M€ oller & Svahn, , 2009Nenonen et al, 2018;Pitelis & Teece, 2018;Salehi et al, 2018;…”
Section: Categorizing Interorganizational Dynamic Capabilitiesmentioning
confidence: 99%
“…The dimensions are built upon the observation, emanating from the body of extant research, that IDCs are discussed and identified in terms of who (Alkalha et al, 2019;Junfeng & Wei-Ping, 2017;Kumar et al, 2018;Lichtenthaler, 2008;Lopez et al, 2012;L€ utjen et al, 2019;Monferrer et al, 2015;Petricevic & Verbeke, 2019;Rajaguru & Matanda, 2019;Rebs et al, 2019;Robertson et al, 2012;Saenz et al, 2014;Vanpoucke et al, 2014;Weerawardena et al, 2015;Zheng et al, 2011) Resource exploitation -Supplier integrative capability -Knowledge acquisition and evaluation -Market-focused learning capability Relationship governance Boundary management -Networking capability -Supplier relationship management capability -Business relationship process management (Allred et al, 2011;Cui et al, 2018;Fehrer & Nenonen, 2020;Forkmann et al, 2016;Helfat & Raubitschek, 2018;Mitrega et al, 2012Mitrega et al, , 2017Mitrega & Pfajfar, 2015;Ngasri & Freeman, 2018;Nordin et al, 2018 (Beske, 2012;Beske et al, 2014;Butler & Soontiens, 2015;Choi et al, 2019;Gruenberg-Bochard & Kreis-Hoyer, 2009;M€ oller & Svahn, 2003M€ oller & Svahn, , 2006M€ oller & Svahn, , 2009Nenonen et al, 2018;Pitelis & Teece, 2018;Salehi et al, 2018;…”
Section: Categorizing Interorganizational Dynamic Capabilitiesmentioning
confidence: 99%
“…Organizational resilience is a strategic imperative to thrive in today's dynamic and interconnected world (Alkalha et al, 2019). It is noticeable that many manufacturing firms had to implement manufacturing-level strategies to adopt production changeover caused by the pandemic to maintain their SC resilience and thus survive (Amui et al, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…For instance, based on Zahra and George's (2002) processes, Alkalha et al. (2019) explored how a company's absorptive capacity can improve supply chain quality, and Saenz et al. (2014) confirmed a positive relationship between absorptive capacity and supply chain innovation and efficiency.…”
Section: Organizational Learning In Logisticsmentioning
confidence: 99%